Cash Waqf Scheme for Equitable Energy Transition in Indonesia’s Transport - Syahputra, Hendra; Syafruddin Kamal; Ilyas, Fithriady (JEJAK, 2024)
Indonesia has significant challenges in funding its energy transition, which requires around US$30 billion over the next eight years. One of the main obstacles is the low government budget and human resource competency in realizing renewable energy to achieve affordability amid rising global energy prices. Islamic financing, particularly cash waqf from Sharia-based institutions, is thought to provide a potential solution. Cash waqf, in line with Islamic principles, generates up to IDR 180 trillion per year and supports the equitable use of renewable energy, especially in transportation. This study utilizes a qualitative descriptive method, through triangulation and comparative techniques. The findings highlight the important role of cash waqf in reducing costs and increasing accessibility to renewable energy for the community. Mechanisms that include cash waqf-based subsidies and innovative financing schemes can be tailored to the transportation sector. By integrating these approaches, Indonesia can reduce reliance on conventional subsidies while promoting inclusive participation in the energy transition. This research underscores cash waqf as a transformative tool, offering a scalable and Sharia-compliant strategy to advance sustainability and equity for policymakers to leverage Islamic finance in achieving a just energy transition, and engaging the role of human capital in managing its sustainability.